Kode vicious cycles on. - Neville-Neil, George (New York ACM, 2005)
Summer has descended upon us, in all of its hot and sticky glory. And as one of our readers reminds us, too much sun can produce strange effects in koders (and those who write about koding). To escape this fate, many take refuge indoors, within the cool confines of industrial-grade, high-power air conditioning. But it's a false haven. It feels great at first, but prolonged exposure can produce deleterious effects, slowing brain activity as workers slowly go all cryogenic. This is disastrous for koders, who suddenly find themselves stumped by the most basic of tasks. Not to worry, though, Kode Vicious knows this feeling and can administer his unique brand of brain-thawing wisdom to the afflicted. It's sure to knock you right out of your frozen stupor. Contact him at kv@acmqueue.com... and turn that darn AC down!
Keywords: General Literature; Miscellaneous; Software; Programming techniques; Language classifications; Object oriented languages; Python; C++.; Computing Methodologies; Document and Text Processing; Document Preparation; Scripting languages; Languages